Analysis of an FDDI network supporting stations with single packet buffers. - Rubin, Izhak (Computer networks and ISDN systems.)
We present exact analysis of a nonsymmetric multiple priority token ring network with single packet buffers under a timed-token protocol, similar to that employed for medium access control of the Fiber Distributed Data Interface (FDDI) network. The single packet buffer model is employed for describing the queueing operation characterizing typical user terminals. An iterative procedure is used to compute the limiting state distribution of the embedded Markov chains representing the system state process. We obtain the distribution of the token rotation time, the normalized throughput, and the mean packet waiting time. By using a counting process representing the numbers of transmitted and deferred packets in a token rotation cycle, we present a simplified analysis of a symmetric network containing a large number of stations. We illustrate the application of the analytic approach through numerical examples representing FDDI network systems operating under various traffic loading conditions.